A Primer on the 'Reproducibility Crisis' and Ways to Fix It. (31st May 2018) - Reed, W. Robert
Abstract: This article uses the framework of Ioannidis (2005 ) to organise a discussion of issues related to the 'reproducibility crisis'. It then goes on to use that framework to evaluate various proposals to fix the problem. Of particular interest is the 'post‐study probability', the probability that a reported research finding represents a true relationship. This probability is inherently unknowable. However, a number of insightful results emerge if we are willing to make some conjectures about reasonable parameter values. Among other things, this analysis demonstrates the important role that replication can play in improving the signal value of empirical research.